2017
DOI: 10.1016/j.ijscr.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

A single thyroid nodule revealing early metastases from clear cell renal carcinoma: case report and review of literature

Abstract: HighlightsMethastases to thyroid gland are a rare condition.RCC (renal cell carcinoma) is the most common primitive tumour which leads to thyroid methastases.Preopeative diagnosis is hard to be established with routinary techniques.Surgical approach (total thyroidectomy) is useful to obtain long survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The thyroid gland is highly vascularised and on this basis one would expect it to be a common site for metastases [ [4] , [5] , [6] , [7] ]. Paradoxically, however, metastases only account for 1–3% of all thyroid malignancies [ [1] , [2] , [3] , [4] , [5] , [6] ]. Protective factors against metastatic deposits in the thyroid gland are thought to be its high concentration of oxygen and iodine, and the filtering capability of pulmonary capillaries [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The thyroid gland is highly vascularised and on this basis one would expect it to be a common site for metastases [ [4] , [5] , [6] , [7] ]. Paradoxically, however, metastases only account for 1–3% of all thyroid malignancies [ [1] , [2] , [3] , [4] , [5] , [6] ]. Protective factors against metastatic deposits in the thyroid gland are thought to be its high concentration of oxygen and iodine, and the filtering capability of pulmonary capillaries [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies have suggested that the commonest primary sources of thyroid metastases are melanoma (39%) and breast carcinoma (21%) [ 3 , 6 , 7 ]. However, a more recent review of clinical cases suggests that renal cell carcinoma now predominates as the leading cause of metastases from non-thyroid malignancies to the thyroid gland (48.1%) [ 1 , 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations